Conciliação e mediação no âmbito da 11ª delegacia regional de polícia civil de Russas/CE no ano de 2018 - Estevam, Osmildo Ferreira (Universidade Federal Rural do Semi-Árido, 2019)
The present article seeks to analyze the methods of conflict self-composition, conciliation and extrajudicial mediation applied to the cases of crimes with less offensive potential and that do not involve the public interest in the poles of the specific case, as means of access to justice in the context of the 11th. Regional Police Station of Civil Police of Russas / CE. From this perspective, bibliographic research will be used in the homeland doctrine and jurisprudence, as well as field research to verify the point of view of those involved in this consensus building process. The work is divided into three chapters. The first makes an analysis of access to justice. The second addresses recent legislation related to the theme: Civil Procedure Code, Mediation Law and Resolution 125 of the CNJ. Finally, it presents and analyzes the numbers of a survey conducted at the 11th Regional Police Station of Russas / CE regarding the application of Conciliation / Mediation in that police unit.
Artigo acadêmico
Keywords: Acesso à Justiça; Conciliação; Mediação; Polícia Civil; Russas; Access to Justice; Conciliation; Mediation; Civil police; Russian; CIENCIAS SOCIAIS APLICADAS::DIREITO